An Anglo-Norman Reader - Bliss, Jane (Open Book Publishers, 2018)
"This book is an anthology with a difference. It presents a distinctive variety of Anglo-Norman works, beginning in the twelfth century and ending in the nineteenth, covering a broad range of genres and writers, introduced in a lively and thought-provoking way. Facing-page translations, into accessible and engaging modern English, are provided throughout, bringing these texts to life for a contemporary audience. The collection offers a selection of fascinating passages, and whole texts, many of which are not anthologised or translated anywhere else. It explores little-known byways of Arthurian legend and stories of real-life crime and punishment; women's voices tell history, write letters, berate pagans; advice is offered on how to win friends and influence people, how to cure people's ailments and how to keep clear of the law; and stories from the Bible are retold with commentary, together with guidance on prayer and confession. Each text is introduced and elucidated with notes and full references, and the material is divided into three main sections based on Dean's Catalogue: Story (a variety of narrative forms), Miscellany (including letters, law and medicine, and other non-fiction), and Religious (saints' lives, sermons, Bible commentary, and prayers). Passages in one genre have been chosen so as to reflect themes or stories that appear in another, so that the book can be enjoyed as a collection or used as a resource to dip into for selected texts. This anthology is essential reading for students and scholars of Anglo-Norman and medieval literature and culture. Wide-ranging and fully referenced, it can be used as a springboard for further study or relished in its own right by readers interested to discover Anglo-Norman literature that was written to amuse, instruct, entertain, or admonish medieval audiences."